Educação física escolar para alunos público-alvo da educação especial nas escolas cívico-militar do Estado de Roraima - Câmara, Leonardo Sobrinho (2022)
The inclusion of students who are the target audience of Special Needs Education in School Physical Education is a great challenge for teachers. This challenge can be faced and conducted so that the participation of these students happens effectively, prioritizing the pedagogical character of the curricular component. With the current process of militarization in state schools in the State of Roraima, the students who are the target audience of Special Needs Education may have been affected concerning their participation in School Physical Education. In this sense, the concern with how School Physical Education happens to students who are the target audience of Special Education guides this study, as the curricular component is fundamental for the process of including these students in the school environment, as well as for their development. Thus, this study aimed to analyze Physical Education for students who are the target audience for Special Needs Education in civic-military schools in the State of Roraima. The research is based on the principles and conceptions of the Cultural-Historical Theory to understand the teaching and learning processes that involve the articulation between Physical Education and Special Education in civic-military schools. The study based on the dialectical and historical materialism method made it possible to understand how School Physical Education happens to students who are the target audience of Special Needs Education in civic-military schools in Roraima, through the construction of data that were the starting point to extract, examine and analyze the elements of such educational reality. The research subjects were, in all, ten teachers of civic-military schools’ Physical Education curricular component in Roraima, using semi-open questionnaires and semi-structured interviews as a tool for data construction. Data was analyzed using the content analysis technique, which follows the stages of organization, coding, categorization, treatment, and interpretation of the collected data. The survey results indicate that most teachers are trained in Physical Education by the Federal Institute of Roraima and State University of Roraima, with specialization in the field of education and have been working as teachers for over 10 years. However, it is identified that only one teacher is specialized in Special Needs Education and three teachers have taken some training course in that field. The students who are the target-audience of Special Needs Education continue to attend civic-military schools after the change from democratic to civic-military management. Regarding the participation of the military in school education, especially in Physical Education, there are disagreements and consensus, mainly because the conceptions of Physical Education and Special Education move between different approaches. There are distinct positions on militarization, but the fact that Physical Education is suffering interference from disciplinary pedagogical proceedings is noteworthy. There is also a need for teacher training that comprehends courses in the field of Special Needs Education, as well as adequate planning with adaptations and specific materials needed, entailing the inclusion of students who are the target audience of Special Needs Education in Physical Education classes. Thus, it is important for teachers to understand the specific educational needs that can promote the development and learning of the target audience of Special Education in Physical Education classes.